ChemInform Abstract: An Alkyne Hydrosilylation—Hiyama Coupling Approach to Highly Functionalized 1, 3‐Dienes. Issue 40 (October 2015) - McAdam, Catherine A.; McLaughlin, Mark G.; Cook, Matthew J.
Abstract Both hydrosilylation and Hiyama coupling give E isomers exclusively.